Pasta revolution : 200 foolproof recipes that go beyond spaghetti and meatballs - Tremblay, Carl; Van Ackere, Daniel (America's Test Kitchen, 2012)
Put away all your preconceived notions about pasta. The test cooks at America's Test Kitchen have stepped up to the stove to take a fresh look at everything pasta, taking nothing for granted and putting everything to the test. The results? New techniques, modern flavors, fresh ways with casseroles, and a host of easier (and sometimes lighter) takes on the classics.